Autophagy: The Last Defense against Cellular Nutritional Stress. Issue 4 (19th July 2018) - He, Long; Zhang, Jie; Zhao, Jinshan; Ma, Ning; Kim, Sung Woo; Qiao, Shiyan; Ma, Xi
Abstract: Homeostasis of nutrient metabolism is critical for maintenance of the normal physiologic status of the cell and the integral health of humans and mammals. In vivo, there is a highly efficient and precise process involved in nutrient recycling and organelle cleaning. This process is named autophagy, and it can be induced in response to the dynamic change of nutrients. When cells face nutritional stress, such as stress caused by nutrient deficiency or nutrient excess, the autophagy pathway will be activated. Generally, when nutrients are withdrawn, cells will sense the signs of starvation and respond. AMP-activated protein kinase and the mammalian target of rapamycin, two of the major metabolic kinases, are responsible for monitoring cellular energy and the concentration of amino acids, respectively. Nutrient excess also induces autophagy, mainly via the reactive oxygen species and endoplasmic reticulum stress pathway. When nutritional stress activates the autophagy pathway, the nutrients or damaged organelles will be recycled for cell survival. However, if autophagy is overwhelmingly induced, autophagic cell death will possibly occur. The balance of the autophagy induction is the crucial factor for cell survival or death. Herein, we summarize the current knowledge on the induction of autophagy, the autophagy response under nutritional stresses, and autophagic cell death and related diseases, which will highlight the process of nutritional stress-induced autophagy and its important physiologic and/or pathologic roles in cell metabolism and diseases, and shed light on the research into the mechanism and clinical applications of autophagy induced by nutritional stresses.